In vitro evaluation of antimicrobial activity of crude extracts of Garcinia griffithii plant against some pathogenic microorganisms - Kamal, Tara; Zuberdi, Ahmad Muzammil; Abdullateef, Raji Akintunde; Rahma, Muayad Salm; Omar, Muhammad Nor (Academic Information Press, 2012)
Nowadays, researchers are focusing their attention towards folk medicine for developing better drugs against microbial infections. The present study aimed to evaluate the inhibitory activity of crude extracts from Garcinia griffithii plant. The plant materials were extracted using solvents with different polarities. The solvent extracts were screened and then tested for antimicrobial activities. It was found that the polar extracts, i.e. methanol and ethyl acetate, showed higher antimicrobial activities than the non polar (Hexane) extract. In previous study, screening test for phytochemicals constituents of the plant showed that, the leaf extract of the plant possessed the active principles e.g. terpenoids, tannins, saponins and glycosides. The antimicrobial activity of the extracts was assayed against four bacteria and two fungal strains using the agar disc diffusion method by indicating the presence of the clear inhibition zones around each disc. Methanolic extract showed the highest inhibition zone of (18±3.4mm) against S. aureus compared with ethyl acetate (10±0.05 mm) and hexane extracts (8±0.05 mm).